Fundamentals of medical imaging - Suetens, Paul (Cambridge University Press, 2002)
Medical imaging has become a very important technology in medical diagnosis and treatment. This book reveals the mathematical and physical principles of medical imaging and image processing--from how medical images are obtained to how they are used. After an introduction to digital image processing, the author explains the most important imaging modalities in use today: Radiography, Computed Tomography, Magnetic Resonance Imaging, Ultrasonic Imaging and Nuclear Medicine Imaging. The remaining chapters cover image analysis and visualization after images are available. A CD packaged with the book includes all of the images in color, and some animated images.